Phyllochron Interval and Yield Response to Planting Date and Fertility in Wheat. Issue 1 (27th October 2016) - Oakes, Joseph; Heiniger, Ronnie; Crozier, Carl; Murphy, Joseph; Wilkerson, Gail
Abstract : Core Ideas: Selecting the proper planting date is crucial in managing early leaf and tiller development while managing temperature. There is an ideal planting date each year that will vary based on weather conditions. Starter fertilizer may be necessary in cold, wet years to stimulate tiller growth. Early growth and fall tiller production are key to high yields. An understanding of early leaf and tiller growth in wheat ( Triticum aestivum L.) and its impact on yield is an important concept for managing winter wheat. Field trials consisting of two planting dates (November and December) and three starter fertilizer treatments (urea ammonium nitrate, ammonium phosphate, Nachurs 9–18–9 liquid fertilizer) were conducted at four locations in North Carolina over a 2‐year period. The earlier planting dates resulted in the highest yield in 2013 to 2014, while the later planting date resulted in the highest yield in 2012 to 2013. Higher yield at the later planting dates in 2012 to 2013 was due to extremely cold weather and less than ideal growing conditions in November that increased the initial phyllochron interval (PI) of the early‐planted wheat. In contrast, ideal growing conditions in December coupled with warm winter weather resulted in a shorter average PI for wheat planted in December than for wheat planted in November. Despite a similar pattern with shorter initial PI at the later plantings in 2013 to 2014, the winter was not as warm and growing degree‐days (GDD) were not accumulated as rapidly as in the previous year, which limited the time that the later planting date had to develop leaves. A response to starter fertilizer was observed at one location in 2013 to 2014, resulting in a shorter PI and higher tiller counts with urea ammonium nitrate and 9–18–9 compared with the control. This resulted in an increased yield, and was largely due to abundant rainfall. This study indicates that planting date and starter fertilizer can influence the length of the initial PI and, depending on subsequent weather, can influence wheat yield.